Visualisasi Skyline Query untuk Distribusi Tenaga Kesehatan COVID-19 - Vega Purwayoga; Muhammad Al Husaini; Hen Hen Lukmana (Maranatha University Press, 2023)
The use of health workers in areas with minimal risk can be a solution to help areas with a high risk of spreading COVID-19. Selection of low risk areas can be done by measuring the level of risk in an area. One solution is to use the skyline query algorithm. Skyline query is able to recommend which areas are potential to serve as supporting areas for health workers. Skyline query is able to produce a recommendation model for determining the supporting area for health workers, however, in the process of reading the information, it is necessary to extract the information. Extraction is carried out by developing a system for visualizing the skyline query as a recommendation system for health personnel assistance. This study develops a visualization system using a hybrid approach, which combines the Rapid GIS Development Cycle (RGDC) and Navigational Development Techniques (NDT) methods. The system was developed using R and the shiny library, ggplot2, rpref and leaflets. The system can work as expected, such as displaying a map of the recommended area to become a supporting area, visualizing data with ggplots and visualizing dominance testing on the skyline query.